Highly Conductive Stretchable and Biocompatible Electrode–Hydrogel Hybrids for Advanced Tissue Engineering. Issue 11 (10th June 2014) - Sasaki, Masato; Karikkineth, Bijoy Chandapillai; Nagamine, Kuniaki; Kaji, Hirokazu; Torimitsu, Keiichi; Nishizawa, Matsuhiko
<x xml:space="preserve">Abstract</x> Hydrogel‐based, molecular permeable electronic devices are considered to be promising for electrical stimulation and recording of living tissues, either in vivo or in vitro. This study reports the fabrication of the first hydrogel‐based devices that remain highly electrically conductive under substantial stretch and bending. Using a simple technique involving a combination of chemical polymerization and electropolymerization of poly (3, 4‐ethylenedioxythiophene) (PEDOT), a tight bonding of a conductive composite of PEDOT and polyurethane (PU) to an elastic double‐network hydrogel is achieved to make fully organic PEDOT/PU–hydrogel hybrids. Their response to repeated bending, mechanical stretching, hydration‐dessication cycles, storage in aqueous condition for up to 6 months, and autoclaving is assessed, demonstrating excellent stability, without any mechanical or electrical damage. The hybrids exhibit a high electrical conductivity of up to 120 S cm−1 at 100% elongation. The adhesion, proliferation, and differentiation of neural and muscle cells cultured on these hybrids are demonstrated, as well as the fabrication of 3D hybrids, advancing the field of tissue engineering with integrated electronics.